DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON THE PROBLEM SOLVING METHOD USING PREZI FOR THE TOPIC OF ENVIRONMENTAL CHANGES - Nafisah Hanim; Zuraidah Zuraidah; Cut Ratna Dewi; Eriawati Eriawati; Ernilasari Ernilasari; Raihanul Muhsan (Universitas Islam Negeri Ar-Raniry, 2024)
The process of learning Biology is still dominated by teachers as the sole source of information, using less interactive teaching media such as chalkboards and textbooks. The use of interactive media is considered appropriate for fostering students' problem-solving abilities, especially in the topic of Environmental Changes. The development of interactive media is crucial. This study aims to develop an interactive learning media using Prezi based on the problem-solving method for the topic of Environmental Changes. The research utilizes the R&D (Research and Development) model following the Borg and Gall research design, with the following stages: potential and problem stage, data collection stage, product design stage, design validation stage, design revision stage, and product revision stage